RETRACTED: Determination of cutting modes when turning railway wheelsets used in heavy traffic - Kononov D.P.; Karaulshchikova E.A. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001